SEMANTIC FEATURES OF PHRASEOLOGICAL UNITS (International journal of artificial intelligence, 2026)
Phraseological units represent one of the most expressive layers of language and play a crucial role in conveying cultural and semantic meanings. This article explores the semantic features of phraseological units, focusing on their idiomaticity, stability, figurativeness, and semantic unity. Phraseological expressions often possess meanings that cannot be deduced from the meanings of their individual components. The research analyzes the semantic characteristics of phraseological units and their role in linguistic communication. The study also highlights the importance of phraseological units in understanding cultural identity and linguistic creativity. The findings show that phraseological units enrich language by providing expressive and culturally bound meanings that go beyond literal interpretation.